Pemikiran Quraish Shihab Tentang Ayat-Ayat Ekonomi - Iswadi, Muhammad (FENOMENA, 2013)
This study was conducted to examine further the commentary of economy passages Quraish Shihabâs work and the thoughts position of Quraish Shihab among other Islamic economic thoughts. This study outlines two theories, namely, (1) theory of economic study; and (2) paradigms and methods of interpretation. Based on the paradigms and methods of interpretation in a social science, economic passage commentary conducted by Quraish Shihab using maudhuâI method is categorized in the social definition paradigm that means contextual and functional commentary. Generally, Islamic economic thoughts of Quraish Shihab belongs to the Islamic economic study in the normative scope which means to the efforts to explain basic philosophy or normative of an economic study which is based on the Islamic guidance referring to the standard guidelines of Qurâan and Hadith. However, in a certain aspect, Quraish Shihabâs thoughts is different from that of mainstream Islamic economic thoughts particularly related to the interpretation of usury which is related to the interest. Quraish Shihab is inclined to think that interest is not the same as usury. However, Quraish Shihab has almost the same thoughts as the mainstream Islamic economic thoughts in terms of Islam and development issues, poverty, alms and alms amyl.